Assessment of the value of measuring soluble fms-like tyrosine kinase-1 and placental growth factor levels following administration of tadalafil to treat fetal growth restriction. (12th December 2022) - Tanaka, Hiroaki; Koide, Keiko; Nakamura, Masamitsu; Maki, Shintaro; Takakura, Sho; Enomoto, Naosuke; Tanaka, Kayo; Katsuragi, Shinji; Sekizawa, Akihiko; Ikeda, Tomoaki
Abstract: Purpose: The aim of this study was to measure the blood levels of soluble fms-like tyrosine kinase-1 (sFlt-1) and placental growth factor (PlGF) before and after tadalafil treatment in patients with fetal growth restriction. Materials and methods: Maternal blood was collected from 13 women before and 2 weeks after tadalafil administration in the TADAFER II trial. The tadalafil treatment was conducted in addition to the conventional FGR treatment. As a control, maternal blood was also collected from 11 women before and 2 weeks after conventional treatment for fetal growth restriction. Blood sFlt-1 and PlGF were measured and the sFlt-1/PlGF ratio was calculated. Student's t -test was used to statistically analyze differences in the sFlt-1 and PlGF levels, and in the sFlt-1/PlGF ratios. Results: In both treatment groups, the levels of sFlt-1 and PlGF before and after treatment were not significantly different from each other. The sFlt-1/PlGF ratio was 2.0 ± 1.0 before and 17.6 ± 11.3 after treatment in the control group ( p =.04). The sFlt-1/PlGF ratio was 2.2 ± 1.1 before and 22.2 ± 10.6 after tadalafil treatment in the tadalafil group ( p =.06). The sFlt-1/PlGF ratios before and after tadalafil treatment were significantly increased in the control group. In both treatment groups, the sFlt-1/PlGF ratios before and after treatment were less than 38. Conclusions: We conclude that the levels of sFlt-1 and PlGF were not significantly different as a result of tadalafil treatment. Further studies are needed to understand the mechanism of action of tadalafil in the treatment of fetal growth restriction.